2010
DOI: 10.1177/1403494810380300
|View full text |Cite
|
Sign up to set email alerts
|

Educational inequalities in ischaemic heart disease mortality in 44,000 Norwegian women and men: The influence of psychosocial and behavioural factors. The HUNT Study

Abstract: Findings from this study indicate that differences in behavioural factors contribute considerably more to inequalities in IHD mortality in educational levels than do psychosocial factors, and this effect seems to be stronger in men than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
2
11
1
1
Order By: Relevance
“…Differences in smoking and hypertension increased between 1984–86 and 2006–08. The investigators also found that 25% of the educational inequalities in CHD mortality in women and 55% in men could be explained by behavioural factors including smoking, physical activity and alcohol intake [40]. We did not observe increasing educational inequalities in AMI incidence during 2001–2009, despite reports on increasing inequalities in risk factors during the same time period.…”
Section: Discussioncontrasting
confidence: 58%
“…Differences in smoking and hypertension increased between 1984–86 and 2006–08. The investigators also found that 25% of the educational inequalities in CHD mortality in women and 55% in men could be explained by behavioural factors including smoking, physical activity and alcohol intake [40]. We did not observe increasing educational inequalities in AMI incidence during 2001–2009, despite reports on increasing inequalities in risk factors during the same time period.…”
Section: Discussioncontrasting
confidence: 58%
“…It is well documented that the distribution of risk factors for IHD differs between social groups [30,31] and that the rates of IHD generally are lower among white-collar workers compared with blue-collar workers. To mitigate the possible influence from uncontrolled risk factors, we decided to only include blue-collar workers in our comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Among these workers, substantial leisure time sitting has also been observed [ 9 , 11 ]. Accordingly, these workers also have a higher prevalence of all-cause mortality and chronic diseases such as ischemic heart diseases compared to white-collar workers [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%